2022
DOI: 10.1039/d1tc04656j
|View full text |Cite
|
Sign up to set email alerts
|

Structure–property relationship study of blue thermally activated delayed fluorescence molecules with different donor and position substitutions: theoretical perspective and molecular design

Abstract: Blue-efficient thermally-activated delayed fluorescence emitters are widely desired in organic light-emitting diodes due to their advantages in both improving display resolution and providing better pixels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
(89 reference statements)
0
19
0
Order By: Relevance
“…In our case the energy-minima D-A angles are all similar (85–89.9°), and so this consideration makes minimal difference to Figure 3 d. In other works though, large differences in relaxed D-A angles between materials (e.g., ∼60° for carbazole, ∼90° for acridine) frustrate direct PES comparison when plotted against absolute D-A angle and absolute (rather than relative) energies at these angles. 44 , 50 , 65 , 66 …”
mentioning
confidence: 99%
“…In our case the energy-minima D-A angles are all similar (85–89.9°), and so this consideration makes minimal difference to Figure 3 d. In other works though, large differences in relaxed D-A angles between materials (e.g., ∼60° for carbazole, ∼90° for acridine) frustrate direct PES comparison when plotted against absolute D-A angle and absolute (rather than relative) energies at these angles. 44 , 50 , 65 , 66 …”
mentioning
confidence: 99%
“…50 More details can be referred to in a previous work. [51][52][53][54][55][56] In addition, analysis of electrostatic potential and interaction region indicators are used to intuitively explore intramolecular halogen bonding, in which IRI function is defined as follows:…”
Section: Theoretical Methods and Calculation Detailsmentioning
confidence: 99%
“…Numerous mechanism investigations support experimental luminescence phenomena and predict the properties of TADF molecules. [31][32][33][34][35][36][37][38][39][40][41][42][43] For example, the Shuai group investigated the TADF mechanism of 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene and found that the rotation of the Cz ligand between two cyano groups leads to the interconversion between S 1 and T 1 . The intramolecular steric hindrance hinders the nonradiative transition of S 1 -S 0 , which in turn enhances the fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…and positions (ortho, meta and para) from a theoretical point of view and predicted several molecules with potential TADF properties. 41 Over the years, boron-based TADF compounds have been continuously developed, and the tri-or tetra-coordinated boron species are the most common. [44][45][46][47][48][49] Among them, the threecoordinated boron atom has an empty p orbital to accept electrons, which is beneficial to the charge transfer process during excitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation